Synthesis and biological evaluation of N-naphthoyl-phenylglyoxamide-based small molecular antimicrobial peptide mimics as novel antimicrobial agents and biofilm inhibitors. Issue 14 (17th March 2016) - Nizalapur, Shashidhar; Ho, Kitty K. K.; Kimyon, Önder; Yee, Eugene; Berry, Thomas; Manefield, Mike; Cranfield, Charles G.; Willcox, Mark; Black, David StC; Kumar, Naresh
Abstract : The synthesis of novel glyoxamide-based antimicrobial peptide mimics is described. Abstract : Antimicrobial peptides (AMPs) are a key component of the human immune system. Synthetic AMP mimics represent a novel strategy to counteract the increasing incidence of antimicrobial resistance. Here, we describe the synthesis of novel glyoxamide derivatives via ring-opening reactions of N -hexanoyl, N -benzoyl and N -naphthoylisatins with N, N -dimethylethane-1, 2-diamine and N, N -dimethylpropane-1, 3-diamine. These were converted to both the hydrochloric acid (HCl) or quaternary ammonium iodide (MeI) salts and their antibacterial activity against Staphylococcus aureus was investigated by their zone-of-inhibition and minimum inhibitory concentration (MIC). The HCl salt22b exhibited the lowest MIC of 16 μg mL −1, whereas the corresponding MeI salt22c had a MIC of 39 μg mL −1 . We also investigated the in vitro toxicity of active compounds against the MRC-5 normal human lung fibroblasts and their activity against established biofilm in S. aureus .